Expansion to abandoned agricultural land forms an integral part of Silver fir dynamics - Volařík, Daniel; Hédl, Radim (Forest ecology and management, 2015)
Silver fir (Abies alba Mill.) is a tree species distributed mainly in central Europe. It once was a dominant tree species within some forests of this region. The causes for its rapid decline in the past two centuries have not yet been sufficiently explained. It is argued that human activities have been largely responsible for expansions and contractions of silver fir populations. On the basis of the current distribution of silver fir, historical maps and palaeoecological data, we describe the expansion of silver fir forests. We use fine resolution at the landscape level, an approach that has so far been neglected. Our study areas lies in the northern part of the White Carpathian Mountains, Czech Republic. The area comprises 7,045 ha, 65% of which is covered by forests. This landscape was shaped by early modern colonization from the 16th century onwards and has changed greatly since the decline of its traditional utilisation in the 19th and 20th centuries. The area of forests almost doubled from 1838 to 2005 while the area of pastures and arable land decreased. We identified 172 hectares of silver fir forests by field mapping, which represent 2.5% of the whole study area and 3.8% of its forested part. We used land use history variables (based on subsequent land cover maps from 1838, 1882 and 1956) and terrain variables (derived from a digital elevation model) in a logistic regression to model the probability of silver fir forest occurrence. Land use history was highly significantly correlated with the occurrence of silver fir forests. Approximately 59% of silver fir forests occur on land used as pastures in 1838, 28% are on former arable land, meadows and fallows, while only 13% have been forested continuously since the 19th century. We know from historical sources that the surrounding forests (now mainly Norway spruce monocultures) were dominated by silver fir up to the 1860s. Silver fir can act as a pioneer species. It can invade former agricultural land, which probably ensures the survival and periodical expansion of silver fir-dominated forests. Although silver fir has been thought to decline under human pressure, we suggest that the opposite may occur at the landscape level.
Keywords: Western Carpathians; silver fir; forest vegetation; species expansion; land use history